Variatio Delectat Consumer Demand for Food Diversity - Silke Thiele; Christoph R. Weiss (Kiel University, Department of Food Economics and Consumption Studies, 2001)
Whereas a large number of empirical studies have been devoted to analysing consumer demand for specific products, much less attention has been paid to the household's demand for product variety (the number of different products consumed in a specific time period). This paper analyses consumer demand for food variety in Germany. The econometric analysis of 4.632 household in 1995 suggests, that variety increases with income and the number of children aged between 6 and 18 years and is significantly higher if the family lives in larger cities in East-Germany, and the housekeeping person is not additionally working full-time. A single male household consumes a significantly smaller number of different food products. The significant (and positive) impact of household income on food variety is in line with the hypothesis that consumption evolves along a hierarchical order as income increases.
Keywords: Q11; D12; 330; Nahrungsmittelkonsum; Produktdifferenzierung; Konsumentenverhalten; Schätzung; Deutschland